Understanding the Utilization of Skills by Returnee Workers in Rupandehi District - Kharal, Hemchandra; Rana, Ashok (International Research Journal of Parroha, 2023)
This qualitative research study aims to understand how returnee workers’ skills are being converted into sustainable earnings by the application of the gained knowledge in different economic activities. The study uses a field survey of returnee workers in Rupandehi District, Nepal, and includes detailed discussions with key stakeholders in the study area. Returnee workers have gained language skills, technical skills, and management skills. These skills are being utilized in different economic activities, including agriculture, tourism, and small businesses. However, returnee workers face challenges related to social reintegration, including cultural differences and a lack of social support. The study recommends that the government should provide support for returnee workers to help them reintegrate into society and utilize their skills effectively. The study’s findings are important because they highlight the need for effective utilization of the skills and knowledge gained by returnee workers to promote sustainable economic growth in Nepal. The study also emphasizes the importance of social support for returnee workers to facilitate their reintegration into society. The study’s recommendations can help the government and other stakeholders to develop policies and programs that support returnee workers and promote sustainable economic growth in Nepal.